Needs of family members of patients with cardiovascular diseases under intensive care - Maicon Henrique Lentsck; Talita Mendes dos Santos; Tatiane Baratieri; Calíope Pilger; Érica de Brito Pitilin; Leticia Gramazio Soares (Universidade Federal do Ceará, 2019)
Objective: to analyze the needs of family members of patients hospitalized for cardiovascular diseases in an intensive care unit. Methods: a cross-sectional study in which the Inventory of Needs and Stressors of Family Members in Intensive Care was applied to 70 family members. Data were analyzed using descriptive statistics. Results: the needs of family members, according to the importance dimension, presented greater emphasis on the safety domain and lesser on comfort. As for the satisfaction dimension, the overall mean was higher in the safety domain and lower in the proximity domain. Conclusion: family needs presented higher means for satisfaction; safety was the best evaluated domain, and comfort and proximity were the worst.